2020
DOI: 10.21511/imfi.17(1).2020.21
|View full text |Cite
|
Sign up to set email alerts
|

Factors of macroeconomic growth in Nigeria: wages demand, taxes, and entrepreneurship development

Abstract: This paper contributes to clarifying the scientific debate on the impact of entrepreneurship development and wages increases on Nigeria’s macroeconomic development. The main purpose of this research is to estimate the impacts, problems, and consequences between wages growth and the growth of a long-term relationship between wages and investment. The article deals with the current state of Nigeria’s macroeconomic indicators. The methodological tools for the research are the ARDL and DOLS methods, which were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The results of the study show that economic growth and real exchange rates are important factors that positively affect the banking system's efficiency, and nonperforming loans impede the efficiency of the banking system in South Africa. Zhuravka et al (2020) profoundly studied the impact of the banking system on macroeconomic growth in Nigeria, i.e. wages demand, taxes, and entrepreneurship development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of the study show that economic growth and real exchange rates are important factors that positively affect the banking system's efficiency, and nonperforming loans impede the efficiency of the banking system in South Africa. Zhuravka et al (2020) profoundly studied the impact of the banking system on macroeconomic growth in Nigeria, i.e. wages demand, taxes, and entrepreneurship development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The role of entrepreneurship in economic development has been widely discussed, with experts stating that entrepreneurship plays a vital role in economic development (Zhuravka et al, 2020). One of Indonesia's interesting mainstay business fields is the pharmaceutical sector, which is included in Indonesia's six mainstay industries (National et al Plan, RIPIN).…”
Section: Introductionmentioning
confidence: 99%
“…Bogatyrev (2021) analyzed the state of entrepreneurship development in the context of the COVID-19 pandemic in his study and, using the classical elements of the theory of comparative analysis and offered an assessment of the efficiency of an enterprise based on updated software. Zhuravka et al (2020) in the periods 1987-2019 assessed the impact of wage growth, investment, and entrepreneurship on the macroeconomic development of Nigeria. The study showed a statistically significant effect of business development and wage growth for the long-term development of Nigeria in the short and long term.…”
Section: Introductionmentioning
confidence: 99%